2022
DOI: 10.1038/s41419-022-05193-x
|View full text |Cite
|
Sign up to set email alerts
|

TREM2/β-catenin attenuates NLRP3 inflammasome-mediated macrophage pyroptosis to promote bacterial clearance of pyogenic bacteria

Abstract: Triggering receptors expressed on myeloid cells 2 (TREM2) is considered a protective factor to protect host from bacterial infection, while how it elicits this role is unclear. In the present study, we demonstrate that deficiency of triggering receptors expressed on myeloid cells 2 (TREM2) significantly enhanced macrophage pyroptosis induced by four common pyogenic bacteria including Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus pneumoniae, and Escherichia coli. TREM2 deficiency also decreased b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Trem2 + macrophages promote bacterial clearance, collagen remodeling, and full-thickness skin regeneration during wound healing. [28,63] Here, it was demonstrated that the recruitment of Trem2 + macrophages on Day 3 was statistically higher in the pGel/M-NIR and MpGel-NIR groups, and the MpGel-NIR group maintained this increase on Day 28, indicating the beneficial recruitment of macrophages by pGO. (Figure 5A,B,E,F and Figure S13, Supporting Information).…”
Section: Mpgel Prevents Scar Formation By Recruiting Trem2 + Macropha...mentioning
confidence: 75%
“…Trem2 + macrophages promote bacterial clearance, collagen remodeling, and full-thickness skin regeneration during wound healing. [28,63] Here, it was demonstrated that the recruitment of Trem2 + macrophages on Day 3 was statistically higher in the pGel/M-NIR and MpGel-NIR groups, and the MpGel-NIR group maintained this increase on Day 28, indicating the beneficial recruitment of macrophages by pGO. (Figure 5A,B,E,F and Figure S13, Supporting Information).…”
Section: Mpgel Prevents Scar Formation By Recruiting Trem2 + Macropha...mentioning
confidence: 75%
“…The role of NLRP3-mediated pyroptosis in podocyte injury was next investigated using MCC950 (NLRP3 inhibitor) ( Tang et al, 2020 ), Ac-YVAD-CMK (caspase-1 inhibitor) ( Wang et al, 2022b ), and nigericin (NLRP3 activator) ( Jian et al, 2020 ; Mo et al, 2021 ). Podocytes were treated with HG in the presence or absence of MCC950, Ac-YVAD-CMK, or nigericin, and then podocyte injury was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…MERC is shown to serve as a signaling hub for NLRP3 inflammasome activation (Horng et al, 2014; Zhou et al, 2020). TREM2 is a direct regulator of the NLRP3 inflammasome and the AD-linked R47H TREM2 variant is not capable of activating the inflammasome (Cosker et al, 2021; Li et al, 2021; Jiang et al, 2022; Wang et al, 2022). These observations further substantiate the idea of the central role for TREM2 in regulating MERC functions.…”
Section: Discussionmentioning
confidence: 99%
“…ITPRIP gene (The gene encoding inositol 1,4,5trisphosphate receptor interacting protein) has also been suggested as an AD risk gene (Simino et al, 2017). AUP1 and REEP5 are known to play a key role in LD biogenesis (Robichaud et al, 2021;Chen et al, 2022), consistent with the functional role for TREM2 in the LD biogenesis. Collectively, our current study provides new insights on TREM2 functions and serves as a foundation for further research aimed at deciphering new molecular players in microglial TREM2 functions.…”
Section: Effects Of R47h Trem2 On the Merc Thicknessmentioning
confidence: 96%